Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1021/acs.jnatprod.7b00747
|View full text |Cite
|
Sign up to set email alerts
|

Antiprotozoal Sesquiterpene Lactones and Other Constituents from Tarchonanthus camphoratus and Schkuhria pinnata

Abstract: In continuation of a search for new antiprotozoal agents from plants of the family Asteraceae, Tarchonanthus camphoratus and Schkuhria pinnata have been investigated. By following the promising in vitro activity of the dichloromethane extracts from their aerial parts, bioassay-guided chromatographic isolation yielded two known sesquiterpene lactones (1 and 2) from T. camphoratus and 20 known compounds of this type from S. pinnata. From the latter, a new eudesmanolide, (1R*,5S*,6R*,7R*,8R*,10R*)-1-hydroxy-8-[5″… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Costunolide is a sesquiterpene lactone (24), which has been reported to exert antiproliferative effects against a wide range of cancer cells, including gastric cancer (25), leukemia (26), colorectal cancer (27) and lung cancer (16). The results of the present study demonstrated that costunolide inhibited the proliferation of H1299 NSCLC cells, with an IC 50 value of 23.93±1.67 µM.…”
Section: Discussionsupporting
confidence: 47%
“…Costunolide is a sesquiterpene lactone (24), which has been reported to exert antiproliferative effects against a wide range of cancer cells, including gastric cancer (25), leukemia (26), colorectal cancer (27) and lung cancer (16). The results of the present study demonstrated that costunolide inhibited the proliferation of H1299 NSCLC cells, with an IC 50 value of 23.93±1.67 µM.…”
Section: Discussionsupporting
confidence: 47%
“…The biological activity of natural sesquiterpenoids has been extensively investigated, including in trypanosomatids [ 24 , 25 , 26 , 27 ]. Initially, we tested total extracts of three Chilean plants and isolated sesquiterpenoids on infective bloodstream trypomastigotes and proliferative epimastigotes.…”
Section: Discussionmentioning
confidence: 99%
“…Essential oil of Guatteria spp., with β ‐eudesmol, γ ‐eudesmol, and α ‐eudesmol as main components, have shown trypanocidal effects on trypomastigotes and epimastigotes of T. cruzi , but this is the first report on their antiparasitic effects when tested alone. Sesquiterpenes from Tarchonanthus camphoratus and Schkuhria pinnata (parthenolide, 3‐oxo‐1,2‐dehydrocostic acid) with structural similarities to sesquiterpenes 1 – 20 showed activity against T. brucei , a clerodane diterpene (related to 13 ) from Polyalthia longifolia and a triterpenoid (with related chemical structure to compounds 33 and 34 ) from Eucalyptus maculata were active on Leishmania mexicana and Trypanosoma brucei . Antiparasitic effects on Plasmodium falciparum due to the inhibition of protein synthesis has been previously reported for holancanthone ( 35 ) …”
Section: Resultsmentioning
confidence: 99%